(untitled) (Journal of the Sociology and Theory of Religion, 2018)
Two events have recently taken place in the Spanish political scene that return the protagonist to the old debate about the use of religious symbols in the takings of possession: on the one hand the absence of religious symbols in the inauguration of Pedro Sánchez and the recent proposal about the need, or opportunity, to legislate a broad and harmonized formulation, for takeovers in Spanish institutions. A contribution to the debate is proposed from a conceptualization of the protocol within the political communication, and an analysis of the historical evolution of the use of religious symbolism in the takings of possession.